Phubbing symptoms creating an anti-social community / Muhammad Nabihan Abu Bakar and Masliya Yahya - Abu Bakar, Muhammad Nabihan; Yahya, Masliya (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Phubbing is the habit of ignoring or snubbing another individual to stay focused on one's cell phone. Unfortunately, this might make the companion feel unimportant, neglected, and frustrated. Phubbing can have a significant impact on a person's friendships, love relationships, and even mental health. Furthermore, phubbing illustrates how technology and human contact are eventually incompatible. People who phub (also known as "phubbers") rarely use their phones for essential calls or emergency emails. More often, they are violating cell phone etiquette by using their phones to entertain themselves in a variety of ways, including scrolling through their social media feeds, posting a selfie or photo of their meal or activity, texting other people and playing online games. All of these behaviours can be damaging to the person who is in direct contact with the phubber. Ultimately, the individual typically believes that the phubber does not care enough about them to focus and pay attention to them.